Dynamic photo-induced force microscopy. Issue 1754 (16th March 2015) - Jahng, Junghoon; Potma, Eric O.
ABSTRACT: We provide a general description of the operating principle of the photo-induced force microscope (PiFM), which probes the optically induced changes in the dipolar interactions between a sharp polarizable tip and the sample, in terms of classical fields and forces. We rigorously calculate the photo-induced force behavior and compare the predicted profile with experimental results obtained from a gold nanowire.